Transmission Biology of Rice Stripe Mosaic Virus by an Efficient Insect Vector Recilia dorsalis (Hemiptera: Cicadellidae) - Yang, Xin; Zhang, Tong; Chen, Biao; Zhou, Guohui (Frontiers in Microbiology, 2017)
Rice stripe mosaic virus (RSMV) is a newly discovered species of cytorhabdovirus infecting rice plants that is transmitted by the leafhopper Recilia dorsalis. In this study, the transmission characteristics of RSMV by R. dorsalis were investigated. Under suitable growth conditions for R. dorsalis, the RSMV acquisition rate reached 71.9% in the second-generation population raised on RSMV-infected rice plants. The minimum acquisition and inoculation access periods of R. dorsalis were 3 and 30 min, respectively. The minimum and maximum latent transmission periods of RSMV in R. dorsalis were 6 and 18 d, respectively, and some R. dorsalis intermittently transmitted RSMV at 2–6 d intervals. Our findings revealed that the virus can replicate in the leafhopper body, but is likely not transovarially transmitted to offspring. These transmission characteristics will help guide the formulation of RSMV prevention and control strategies.